Aplicação de texto paradidático no ensino de física como possível alternativa para a inclusão de aluno com deficiência visual - Evangelista, Carla Reis [UNESP]; Camargo, Eder Pires de [UNESP]; Anjos, Paola Trama Alves dos [UNESP] (My University, 2011)
The work completed on the use of para-didactic texts do not address the issue of education in a state that considers the presence of students with visual impairments. Therefore, this article discusses an innovative situation, investigating if the use of para-didactic texts provide the necessary conditions for the inclusion of students with visual impairment in physics education classes. The response indicates a discreet participation of these students, however a significant one, in this application the students were motivated and interested in all of the topics discussed. This prudent participation may have occurred for reasons such as shyness and the behavior of teachers, as they tended to to be more talkative to these students.

Os trabalhos realizados sobre a utilização de textos paradidáticos não enfocam a problemática do ensino em situação que contemple a presença de alunos com deficiência visual. Portanto, o presente artigo aborda uma situação inovadora, investigando se a utilização de textos paradidáticos proporciona condições de inclusão do aluno com deficiência visual em aulas de física. A resposta indica uma participação discreta desse aluno, mas significativa, pois nesta o discente mostrou-se motivado e interado dos temas abordados. Esta participação discreta pode ter ocorrido por motivos como timidez e condutas do docente no sentido de atribuir a palavra com mais frequência ao discente.
Application of para-didactic texts in physics education as an alternative to include students with visual impairments
Keywords: Teaching of physics education; Para-didactic text; Visual impairment; Ensino de física; Texto paradidático; Deficiência visual